Changes in Phytochemical Content, Antioxidant Activity, and Anti-Inflammatory Properties of Cudrania tricuspidata Fruits Treated by Roasting - Si Young Ha; Ji Young Jung; Jae-Kyung Yang (Foods, 2023)
The study investigated the antioxidant effects of roasted Cudrania tricuspidata (C. tricuspidata) fruits by comparing them with unroasted C. tricuspidata fruits. The results showed that the roasted C. tricuspidata fruits (150 °C, 120 min) exhibited significantly higher antioxidant activity, especially in terms of anti-inflammatory effects, than the unroasted fruits. Interestingly, there is a high correlation between the color of the roasted fruit and the antioxidant activity. Heating disrupts cells and deactivates endogenous oxidative enzymes, leading to an increase in flavonoid content. Moreover, heat treatment may also interfere with plant metabolism, thereby influencing flavonoid content. Moreover, an HPLC analysis of roasted fruits in our study showed that the increase in antioxidant activity was attributed to the increase in flavan-3-ols and phenolic acids in the roasted C. tricuspidata fruits. To the best of our knowledge, this is the first time the antioxidant activity and anti-inflammation of roasted C. tricuspidata fruits was studied. The study concluded that roasted C. tricuspidata fruits could be a valuable natural source of antioxidants for various food and medicinal applications.